Telomerase and myocardin co-expressing mesenchymal cells increase survival and induce cardiac and vascular markers in cardiac stromal cells undergoing simulated ischemia/reperfusion. (14th October 2021) - Madonna, R; Guarnieri, S; Csenger Kovacshazi, C; Gorbe, A; Giricz, Z; Geng, Y J; Mariggio, M A; Ferdinandy, P; De Caterina, R
Abstract: Background: Cardiac stromal cells (CSCs) contain a pool of cells with supportive and paracrine functions. Various types of mesenchymal stromal cells (MSCs) can influence CSCs in the cardiac niche through their paracrine activity. Ischemia/reperfusion (I/R) leads to cell death and reduction of the paracrine activity of CSCs. The forced coexpression of telomerase reverse transcriptase (TERT) and myocardin (MYOCD), known to potentiate anti-apoptotic, pro-survival and pro-angiogenic activities of MSCs isolated from the adipose tissue (AT-MSCs), may increase CSC survival, favoring their paracrine activities. Aim: To investigate the hypothesis that CSCs feature improved resistance to simulated I/R (SI/R) and increased commitment toward the cardiovascular lineage when preconditioned with conditioned media (CM) or extracellular vesicles (EV) released from AT-MSCs overexpressing TERT and MYOCD (T/M AT-MSCs). Methods and results: Murine CSCs were isolated with the cardiosphere (CSps) isolation technique. T/M AT-MSCs and their secretome improved spontaneous intracellular calcium changes and ryanodine receptor expression in aged CSps. The cytoprotective effect of AT-MSCs was tested in CSCs subjected to SI/R. SI/R induced cell death as compared to normoxia (28±4 vs 10±3%, p=0.02). Pretreatment with CM (15±2, p=0.02) or with the EV-enriched fraction (10±1%, p=0.02) obtained from mock-transduced AT-MSCs in normoxia reduced cell death after SI/R. The effect was more prononunced with CM (7±1%, p=0.01) or the EV-enriched fraction (2±1%, p=0.01) obtained from T/M AT-MSCs subjected to SI/R. In parallel, we observed lower expression of the apoptosis marker cleaved caspase-3 and higher expression of cardiac and vascular markers eNOS, sarcomeric α-actinin and cardiac actin. Conclusions: The T/M AT-MSCs secretome exerts a cytoprotective effect and promotes development of CSCs undergoing SI/R towards a cardiovascular phenotype. Funding Acknowledgement: Type of funding sources: None.